Daun Katub (Sauropus androgynus (L.) Merr) Meningkatkan Produksi Air Susu Ibu - Handayani, Sri; Pratiwi, Yopi Suryatim; Ulya, Yadul (Jurnal Ilmiah STIKES Yarsi Mataram, 2021)
The infant mortality rate is still high in Indonesia and is reduced through offering exclusive breastfeeding. The achievement of exclusive breastfeeding in Indonesia is still far from the national target, one of which is due to insufficient breast milk production. Katuk leaves are a plant that cannot increase milk production. Therefore we need scientific evidence that uses katuk leaves as a lactogogue. This article is a literature review that aims to see the effect of katuk leaves on increasing breast milk production. Based on the research results, katuk leaves can increase breast milk production. This is because katuk leaves contain active compounds, namely papaverine and phytosterols and contain high nutrients.